2018
DOI: 10.1515/hsz-2017-0280
|View full text |Cite
|
Sign up to set email alerts
|

The neutral sphingomyelinase 2 in T cell receptor signaling and polarity

Abstract: By hydrolyzing its substrate sphingomyelin at the cytosolic leaflet of cellular membranes, the neutral sphingomyelinase 2 (NSM2) generates microdomains which serve as docking sites for signaling proteins and thereby, functions to regulate signal relay. This has been particularly studied in cellular stress responses while the regulatory role of this enzyme in the immune cell compartment has only recently emerged. In T cells, phenotypic polarization by co-ordinated cytoskeletal remodeling is central to motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…In accordance, pharmacological or genetic ablation of neutral sphingomyelinase 2 interfered with T cell polarization, suggesting that neutral sphingomyelinases are involved in T cell recruitment and migration (99,100). Besides regulation of T cell polarization and migration, neutral sphingomyelinase-2 is also critically involved in fine-tuning of signaling generated via the TCR/CD3 (99,100). Thus, deletion of neutral sphingomyelinase-2 resulted in hyper-responsivity of T cells upon stimulation via CD3/CD28 (99,100).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 79%
See 2 more Smart Citations
“…In accordance, pharmacological or genetic ablation of neutral sphingomyelinase 2 interfered with T cell polarization, suggesting that neutral sphingomyelinases are involved in T cell recruitment and migration (99,100). Besides regulation of T cell polarization and migration, neutral sphingomyelinase-2 is also critically involved in fine-tuning of signaling generated via the TCR/CD3 (99,100). Thus, deletion of neutral sphingomyelinase-2 resulted in hyper-responsivity of T cells upon stimulation via CD3/CD28 (99,100).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 79%
“…Several studies imply that also neutral sphingomyelinases are important in T cell activation ( 100 , 101 ). These studies demonstrated that inhibition of neutral sphingomyelinases interfered with lymph node homing and adhesion of T cells to activated endothelial cells ( 99 , 100 ). In accordance, pharmacological or genetic ablation of neutral sphingomyelinase 2 interfered with T cell polarization, suggesting that neutral sphingomyelinases are involved in T cell recruitment and migration ( 99 , 100 ).…”
Section: Sphingolipids In Autoimmune Lymphocyte Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stage, the formation of T lymphocytes is dependent on a strong activation signal involving the T cell receptor (TCR) and co-stimulatory signal from the CD28 molecule, a process mediated by SMase activity. In turn, NSMase2 generates microdomains, regulating the signal relay for signalling proteins [97]. Activation of CD3 enhances NSMase2 production, while CD28 stimulates aSMase [98][99][100].…”
Section: Sphingolipid Action In Inflammation-focus On the Molecular Mmentioning
confidence: 99%
“…Morphological polarization associated with that of receptors is of obvious importance for spatial perception of chemoattractants. NSM2-deficient CD4 + T cells largely failed to polarize and to redistribute CXCR4 and thus, not surprisingly, were substantially impaired in directional migration and velocity in response to SDF-1α or in collagen matrices (mimicking extracellular matrix or tissue interaction) (Collenburg et al, 2017, 2018). Though not detectably affecting morphological polarization, pharmacological NSM2 inhibition also ablated directionality of human polymorphonuclear neutrophils (PMNs) in response to formyl methionine leucyl phenylalanine (FMLP), but not their overall motility (Sitrin et al, 2011).…”
Section: Impact Of Asm/nsm2 Activity On T-cell Motility and Tissue Homentioning
confidence: 99%